2014
DOI: 10.1007/s12031-014-0248-0
|View full text |Cite
|
Sign up to set email alerts
|

PACAP38 and PACAP6-38 Exert Cytotoxic Activity Against Human Retinoblastoma Y79 Cells

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a multifunctional neuropeptide expression of which has been found in various tumors of the brain and peripheral organs. Despite numerous studies, the exact role the peptide plays in the development and progression of tumors is not fully understood. In the present study, we investigated the effect of PACAP on human retinoblastoma Y79 cell viability. We found that both PACAP38 and PACAP6-38, a selective PAC1 receptor antagonist, did not affect Y79 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
(43 reference statements)
4
25
0
Order By: Relevance
“…The reason for this is not known at the moment, and may or may not reflect the physiological role of the peptide, since these experiments were performed in choriocarcinoma cells, in which the receptor expression and signaling induced by PACAP may be significantly altered. Similar results were described in retinoblastoma cells, where PACAP treatment induced cell death [55] in spite of the well-known protective effects of PACAP in the retina [56,57]. PACAP also inhibited the growth of the neuronal tumor medulloblastoma in spite of the well-known neuroprotective effects of the peptide [58][59][60].…”
Section: Effects Of Pacap On Survival Of Trophoblast Cellssupporting
confidence: 80%
See 1 more Smart Citation
“…The reason for this is not known at the moment, and may or may not reflect the physiological role of the peptide, since these experiments were performed in choriocarcinoma cells, in which the receptor expression and signaling induced by PACAP may be significantly altered. Similar results were described in retinoblastoma cells, where PACAP treatment induced cell death [55] in spite of the well-known protective effects of PACAP in the retina [56,57]. PACAP also inhibited the growth of the neuronal tumor medulloblastoma in spite of the well-known neuroprotective effects of the peptide [58][59][60].…”
Section: Effects Of Pacap On Survival Of Trophoblast Cellssupporting
confidence: 80%
“…This does not seem to be specific for this cell line, since agonistic effects were found for example on rat trachea neuropeptide release, retinoblastoma cell survival and cartilage and bone development [55,[62][63][64]. The reason for this might be the expression of a yet unknown splice variant of the receptor or the tumorous nature of the JAR cells.…”
Section: Effects Of Pacap On Survival Of Trophoblast Cellsmentioning
confidence: 94%
“…Interestingly, PACAP1-27 and maxadilan had negligible effects, while two membrane-penetrating analogs of PACAP also decreased cell viability. The authors also revealed that this cytotoxic effect might be via an interaction of p38, MEK1/2, and JNK signaling, because inhibitors of these pathways led to an even more expressed cytotoxicity [ 115 ]. These results suggest that high concentrations of PACAP1-38 might lead to a transmembrane penetration and lead to direct cytotoxicity at sites other than the conventional PACAP receptor-mediated signaling.…”
Section: Studies In Tumor Cellsmentioning
confidence: 92%
“…These results provide evidence that PACAP1-38 has neuroprotective effects in hypoxic/ anoxic conditions in the adult turtle retina in vitro. Nanomolar: no effect on cell viability Micromolar: ↓: Cell viability, further ↓: with PACAP6-38; no effect: PACAP1-27 and maxadilan [ 115 ] …”
Section: In Vitro Protective Effects In the Neural Retinamentioning
confidence: 97%
See 1 more Smart Citation